The Literary Style of Hittite Mythological Texts - DeVries, Bert (1967)
Dissertation; offers new translations of Hittite mythological texts which have not been translated into English and plot summaries of the rest. The texts are subjected to a detailed grammatical analysis in which special attention is paid to stylistic matters. Significant differences in grammar and style are indicated between the myths of Hattic and Hurrian origin. A final chapter treats matters of content (motifs, etc.); Supervisor: Harry A. Hoffner, Jr. Obtainable through University Microfilms, Ann Arbor, Mich., U.S.A.